Badantam Traditions in Marriage in Korong Koto Rajo Nagari Sunur Tengah, Nan Sabaris District, Padang Pariaman Regency - Sosa, Sosa Hijria Audia; Suharti; Yurisman (Kirana Publisher (KNPub), 2023)
This thesis is entitled